THE STUDENTS’ STRATEGY IN APPLYING COGNITIVE ACADEMIC LANGUAGE LEARNING APPROACH (CALLA) FOR READING ANALYTICAL EXPOSITION TEXT - Novita Eka Tristiana (Politeknik Negeri Bengkalis, 2016)
Abstract: The research was conducted to pinpoint the students’ reading strategies when they apply cognitive academic language learning approach (CALLA) instructional reading strategies in reading analytical exposition text. The research used qualitative approach which involved the case study method. The participants involved in this research were the 11th Class MIA3 students at SMAN 2 Pringsewu, Lampung. In collecting the data the teacher used think-aloud protocol, observation and questionnaire. The result of this study show that in applying CALLA instructional reading strategy, the students used the entire of three primary of reading strategies suggested in CALLA such as; meta-cognitive strategy, cognitive strategy and social - affective strategy in reading analytical exposition text. The researcher suggested to the teacher to apply the instructional reading strategy in teaching reading. Finally, the researcher suggested the students to know many kinds of reading strategies that could be applied in comprehending the analytical exposition text.Key words: reading strategy, analytical exposition, CALLA instructional reading strategy